Spiritualitas dan Integritas Pelayan Tuhan dalam Menghadapi Disrupsi Etika di Era Informasi Digital - Paskalin, Christina Aprilliani; Boiliu, Esti Regina (Sekolah Agama Kristen Terpadu Pesat Salatiga, 2025)
The development of information technology and social media in this era of disruption has had a major impact on religious practices. On the one hand, digital advances have opened up new opportunities for churches to expand their ministries, but on the other hand, there are also serious challenges that touch on the ethical, moral and spiritual aspects of the congregation. The challenges faced by ministers of God in maintaining spirituality and integrity amid ethical disruption caused by the development of information technology. The purpose of this study focuses on Christian ethical challenges in the use of social media and efforts to formulate strategies for spiritual guidance of congregations to remain faithful to Christ's teachings amid the rapid flow of digitalisation. Using qualitative research methods with a literature study approach, it can be concluded that the development of information technology presents great opportunities for Christian ministry, but also poses serious challenges in the form of ethical disruption. Social media can be a means of spreading the gospel and fellowship of faith, but if misused, it can damage the spirituality and integrity of the congregation. Therefore, ministers need to develop Christian ethics-based digital literacy by setting an example in the wise use of technology. Christian ethics education in the digital space is important to shape congregations that are able to sort information, avoid hoaxes, and use social media as a means of witnessing their faith.AbstrakPerkembangan teknologi informasi dan media sosial di era disrupsi telah membawa pengaruh besar dalam praktik keagamaan. Di satu sisi, kemajuan digital membuka peluang baru bagi gereja untuk memperluas pelayanan, namun di sisi lain, hadir pula tantangan serius yang menyentuh aspek etika, moral, dan spiritualitas jemaat. Adapun tantangan yang dihadapi oleh pelayan Tuhan dalam mempertahankan spiritualitas dan integritas di tengah disrupsi etika akibat perkembangan teknologi informasi. Tujuan penelitian ini berfokus pada tantangan etika Kristen dalam penggunaan media sosial serta upaya merumuskan strategi pembinaan rohani jemaat agar tetap setia kepada ajaran Kristus di tengah derasnya arus digitalisasi. Menggunakan metode penelitian kualitatif dengan pendekatan studi pustaka maka dapat disimpulkan bahwa Perkembangan teknologi informasi menghadirkan peluang besar bagi pelayanan Kristen, namun juga menimbulkan tantangan serius berupa disrupsi etika. Media sosial dapat menjadi sarana penyebaran Injil dan persekutuan iman, tetapi jika disalahgunakan dapat merusak spiritualitas dan integritas umat. Oleh karena itu, pelayan Tuhan perlu mengembangkan literasi digital berbasis etika Kristen dengan menjadi teladan dalam penggunaan teknologi secara bijak.